KINERJA PERUSAHAAN UMUM DAERAH (PUD) PASAR KOTA MEDAN DALAM PENGELOLAAN PASAR TRADISIONAL - Butarbutar, Veronica; Ridwan, Mohammad (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to determine the performance of the Medan City Regional Public Market Company in managing the Sei Sikambing traditional market. This research is useful for providing information so that the municipalities can manage traditional markets and optimize market levy revenues to increase Regional Original Income. This research uses descriptive research using qualitative analysis. Data collection techniques through observation, documentation, interviews, and literature review. The results of this study show that Medan City Market Regional Public Company is not optimal for the management of the Sei Sikambing market. It shows performance indicators, namely productivity, service quality, and responsiveness. Productivity indicators are still not optimal because there are still some obstacles that have not been resolved, so the marketing fee revenue target has not been met. The quality of the services provided is sufficient but needs to be improved by improving market facilities and infrastructure that support improving service quality. Responsiveness is still less than optimal because all the needs required by traders cannot be fully addressed. Apart from that, the Medan City Market Regional Public Company faces several obstacles in managing the market, namely: 1) There are no regional regulations that have been passed regarding the management of street vendors, 2) the implementation of the duties of each market management authority is still not optimal, 3) the budget is not optimal. limited in supporting traditional market management. Keywords: Public Management; Performance; Regional Public Company; Service Quality; Productivity